Biosorption Of Colour In Landfill Leachate Using Acid Pre-Treated Hydrilla Verticillata - Roslan, Muhamad Amir Idham (Universiti Sains Malaysia, 2022)
Leachate from landfills is a complex fluid with a wide range of amounts and structures in fluid content, chemical composition, and others. It also contains high amounts of biodegradable and nonbiodegradable compounds such as organic matter, phenols, ammoniacal nitrogen, phosphate, heavy metals, and sulphide, as well as strong colour and unpleasant odour. Several treatment systems have been designed for leachate colour removal, but each treatment system has its own limitations, especially concerning low efficiency, production of secondary waste, and high operational cost. A study on various biosorbents in promoting environmental and economic sustainability has become a current attempt by researchers to remove the colour of leachate from landfills. Consequently, biosorption using low-cost biomass like H. verticillata had shown promising results in colour removal but somehow was less research for tropical aquatic plant species. Therefore, this study was conducted to evaluate the potential of H. verticillata to be used as a biosorbent for removing colour in landfill leachate. The techniques characterizing H. verticillata on their colour removal percentage (R%). Studies have been made on the effect of pre-treatment on the biosorbent in order to investigate the biosorption capacity. Characterization of biosorbent was determined by Fourier Transform Infrared Spectrophotometer (FT-IR), Brunauer-Emmett-Teller (BET) and Zeta Potential Measurement. Biosorption using batch study mode was further examined for the effect of various operational parameters such as contact time (20-100min), pH (2–6), and biosorbent dosage (1.0–5.0 g/L). The results reveal that the equilibrium time for H. verticillata can be achieved within 60min at room temperature. H. verticillata with pre-treatment with HCL process was used for the entire experiment did not enhance the uptake capacity of H. verticillata since the percentage removal of colour obtained after treatment leachate was significantly very low. The adsorption is otherm data show that the Langmuir was better fitted than the Freundlich isotherm model. The kinetic data, however, were better fitted to the pseudo-first-order kinetic model. In conclusion, red seaweed of H. verticillata with pre-treatment with acid was found to have a low potential as an alternative natural occurring biosorbent specifically for the colour of landfill leachate. Different activation techniques on H. verticillata are recommended to enhance the removal of colour from landfill leachate solution since it has the potential to become a sustainable, greener biosorbent for future applications.